Hemodynamic and clinical onset in patients with hereditary pulmonary arterial hypertension and BMPR2 mutations - Pfarr, Nicole; Szamalek-Hoegel, Justyna; Fischer, Christine; Hinderhofer, Katrin; Nagel, Christian; Benjamin, Nicola; Tiede, Henning; Olschewski, Horst; Reichenberger, Frank; Ghofrani, Ardeschir H. A.; Seeger, Werner; Grünig, Ekkehard (Respiratory research, 2011)
BACKGROUND: Mutations in the bone morphogenetic protein receptor 2 (BMPR2) gene can lead to idiopathic pulmonary arterial hypertension (IPAH). This study prospectively screened for BMPR2 mutations in a large cohort of PAH-patients and compared clinical features between BMPR2 mutation carriers and non-carriers. - METHODS: Patients have been assessed by right heart catheterization and genetic testing. In all patients a detailed family history and pedigree analysis have been obtained. We compared age at diagnosis and hemodynamic parameters between carriers and non-carriers of BMPR2 mutations. In non-carriers with familial aggregation of PAH further genes/gene regions as the BMPR2 promoter region, the ACVRL1, Endoglin, and SMAD8 genes have been analysed. - RESULTS: Of the 231 index patients 22 revealed a confirmed familial aggregation of the disease (HPAH), 209 patients had sporadic IPAH. In 49 patients (86.3% of patients with familial aggregation and 14.3% of sporadic IPAH) mutations of the BMPR2 gene have been identified. Twelve BMPR2 mutations and 3 unclassified sequence variants have not yet been described before. Mutation carriers were significantly younger at diagnosis than non-carriers (38.53 ± 12.38 vs. 45.78 ± 11.32 years, p < 0.001) and had a more severe hemodynamic compromise. No gene defects have been detected in 3 patients with HPAH. - CONCLUSION: This study identified in a large prospectively assessed cohort of PAH- patients new BMPR2 mutations, which have not been described before and confirmed previous findings that mutation carriers are younger at diagnosis with a more severe hemodynamic compromise. Thus, screening for BMPR2 mutations may be clinically useful.
Gesehen am 08.12.2022